A Numerical Simulation of Extratropical Storm Surge and Hydrodynamic Response in the Bohai Sea - Yumei Ding; Lei Ding (Discrete Dynamics in Nature and Society)
A hindcast of typical extratropical storm surge occurring in the Bohai Sea in October 2003 is performed using a three-dimensional (3D) Finite Volume Coastal Ocean Model (FVCOM). The storm surge model is forced by 10 m winds obtained from the Weather Research Forecasting (WRF) model simulation. It is shown that the simulated storm surge and tides agree well with the observations. The nonlinear interaction between the surge and astronomical tides, the spatial distribution of the maximum surge level, and the hydrodynamic response to the storm surge are studied. The storm surge is the interaction of the surge and the astronomical tides. The currents change rapidly during the storm surge and turn to be the unidirectional at some places where the tidal currents are usually rectilinear. The results show that the local surge current velocity in each depth, with a magnitude of the same order as the astronomic tidal currents, increases or decreases rapidly depending on the relationship between the winds and current directions. Furthermore, the current pattern gets more complicated under the influence of the direction of the winds, which might affect sand movement in the coastal water of the Bohai Sea.